Food Sources of Sodium in Korean Americans With Type 2 Diabetes: Implications for Cardiovascular Disease. (March 2019) - Ko, Jisook; Timmerman, Gayle M.; Kim, Kim B.; Kim, Miyong T.
Introduction: Excess sodium intake can increase the risk of high blood pressure and cardiovascular disease, common comorbidities for those with type 2 diabetes mellitus (T2DM). The purpose of this study is to describe sodium intake and high sodium food sources among Korean Americans (KAs) with T2DM.Method: This study, a descriptive, secondary analysis of baseline data from a clinical trial for diabetes, recruited KAs with T2DM ( n = 232) from the community.Results: Average dietary sodium intake was 3, 433 mg. Major sources of dietary sodium were from bicultural diets: noodles and dumplings, Korean-style soups, kimchi, breads and snacks, and boiled or seasoned vegetables. Participants who consumed excessive sodium were more likely to consume more calories and be male, married, and more recently diagnosed with T2DM.Discussion: High consumption of sodium among KAs with T2DM supports the need to develop effective, tailored interventions addressing dietary sodium that incorporates the individual's culture.